Perceived Effectiveness of KPT-PACE Instructional Materials in Fostering Communication Competence - Mohamed Mokhtar, Mazlin; Mohd Khaja, Farah Natchiar; Madzlan, Noor Alhusna; Qalbi Ahamad, Siti Khairani; Zulazli, Arif Hakimi; Aziq Sua'if, Amirul (Forum for Linguistic Studies, 2025)
This study investigates university students' perceptions of the KPT-PACE instructional materials for developing their communication skills. Using a quantitative approach, data were collected from 112 students across different academic disciplines who had experienced the KPT-PACE program. The research specifically examined the materials' effectiveness in three key communication domains: speaking, listening, and vocabulary. Descriptive and inferential statistical analyses were applied to interpret the students' feedback. The findings indicate that students viewed the instructional materials positively, with speaking skills receiving the highest mean score (M = 3.33), followed by listening (M = 3.15) and vocabulary (M = 3.14). Each domain demonstrated statistically significant results above the neutral value of 3 (p < 0.001), suggesting that students perceived notable improvement in their communication abilities through the use of these materials. Among the three areas, speaking emerged as the most impacted, reflecting the strength of the materials in promoting oral proficiency. Overall, the results support the view that the KPT-PACE instructional materials are effective tools for enhancing communication skills among university learners. These insights may guide future improvements in curriculum design and material development, contributing to more targeted and impactful communication instruction in higher education settings.